Risk factors of inadequate bowel preparation for screening colonoscopy - Amitay, Efrat L.; Niedermaier, Tobias; Gies, Anton; Hoffmeister, Michael; Brenner, Hermann (Journal of Clinical Medicine, 2021)
The success of a colonoscopy in detecting and removing pre-cancerous and cancerous lesions depends heavily on the quality of bowel preparation. Despite efforts, 20-44% of colonoscopy participants have an inadequate bowel preparation. We aimed to assess and compare risk factors for inadequate bowel preparation and for the presence of advanced colorectal neoplasms in routine screening practice. In this cross-sectional study, among 8125 participants of screening colonoscopy in Germany with a comprehensive assessment of sociodemographic factors, lifestyle and medical history, we examined factors associated with inadequate bowel preparation and with findings of advanced neoplasms using adjusted log-binomial regression models. Among the identified risk factors assessed, three factors were identified that were significantly associated with inadequate bowel preparation: age ≥ 70 years (adjusted prevalence ratios, aPR, 1.50 95%CI 1.31-1.71), smoking (aPR 1.29 95%CI 1.11-1.50) and abdominal symptoms (aPR 1.14 95%CI 1.02-1.27). The same risk factors were also associated with the prevalence of advanced neoplasms in our study (aPR 1.72, 1.62 and 1.44, respectively). The risk factors associated with inadequate bowel preparation in this study were also associated with a higher risk for advanced neoplasms. Inadequate bowel preparation for colonoscopy might lead to missed colorectal cancer (CRC) precursors and the late diagnosis of CRC. People at high risk of advanced neoplasms are in particular need of enhanced bowel preparation.